PENGARUH MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KETENAGAKERJAAN CABANG SUDIRMAN JAKARTA - Kunto Atmojo; Erik Pradana (Sekolah Tinggi Manajemen IMMI Jakarta, 2019)
The purpose of this study was to determine the effect of motivation on employee performance at the Sudirman Branch Social Security Administrators (BPJS). The data analysis technique used is quantitative analysis to be able to determine the effect of motivation on performance with 56 respondents. Methods of data collection analysis using validity test, reliability test, correlation coefficient test, determination coefficient, simple regression correlation and hypothesis testing. The influence of motivation on employee performance based on the calculation of the correlation coefficient, the value of 0.877 means that the influence of motivation on employee performance is said to be very strong. From the calculation of the coefficient of determination (KD), the value is 0.768, this shows that the amount of motivation contribution to employee performance is 76.8%, while the rest (100% -76.8%) = 23.2% is influenced by other factors. Based on the test results, tcount ttable is 13.388 2.005, which means that Ho is rejected and Ha is accepted, meaning that there is a positive and significant influence between motivation (X) on employee performance (Y) at the Sudirman Jakarta branch of the Social Security Administration (BPJSTK).